Desarrollo del sistema financiero y su contribución en los niveles de crecimiento económico del Ecuador periodo 2015-2020. - Merizalde Peñafiel, Alicia Mercedes; Zapata Mateo, Adriana Betsy (Machala : Universidad Técnica de Machala, 2022)
The financial system is one of the fundamental pillars for boosting the economy and fostering economic growth. For this reason, the present study aims to analyze the influence of the financial system on the economic growth of Ecuador in the period 2015-2020. Mainly identifying the contribution to total GDP, followed by other economic and financial indicators. For this, a documentary-descriptive methodology is applied that allows obtaining numerical information and qualities related to the research topic. Among the methods applied, the historical-logical and the deductive stand out. The results of the investigation show a decrease in the gross domestic product of -3.4% for the last 5 years, along with an active rate of 8.35% and a passive rate of 5.54%. The credit volume decreased in 2020 by $1,120.02 million USD compared to the previous year. The 3 segments where the system grants credits the most is commercial with 71%, consumption with 19% and microcredits with 7%, all these data valued at the year 2020. With respect to technical equity, an oligopolistic banking system is evident where 4 of the 24 banks have the greatest participation, giving a total value of $3,552,519,434 in US dollars. The contribution of the financial system to total GDP had two negative periods in 2015 and 2020 with a figure of -0.06% and -0.09%.
El sistema financiero es uno de los pilares fundamentales para dinamizar la economía y propiciar el crecimiento económico. Por ello el presente estudio tiene por objetivo analizar la influencia del sistema financiero en el crecimiento económico del Ecuador en el período 2015-2020. Identificando principalmente el aporte al total del PIB, seguido de otros indicadores económicos y financieros. Para esto se aplica una metodología documental-descriptiva que permite obtener información numérica y cualidades relacionadas al tema de investigación. Entre los métodos aplicados destacan el histórico-lógico y el deductivo. Los resultados de la investigación evidencian un decrecimiento del producto interno bruto en -3,4% para los últimos 5 años, a la par una tasa activa del 8,50% y una pasiva del 5,89% para el 2020. El volumen de crédito decreció en el 2020 en $ 1.120,02 millones de USD con respecto al año anterior. Los 3 segmentos donde más el sistema otorga créditos es en el comercial con el 71%, consumo con el 19% y microcréditos con el 7% todos estos datos valorados al año 2020. Con respecto al patrimonio técnico se evidencia un sistema bancario oligopólico donde 4 de los 24 bancos tienen mayor participación dando como total el valor de $ 3.552.519.434 en dólares americanos. El aporte del sistema financiero al total del PIB tuvo dos periodos negativos en el 2015 y 2020 con una cifra del -0,06% y -0,09%.
Keywords: SISTEMA FINANCIERO; CRISIS; OLIGOPOLIO; INTERES